BUNYI MUSICAL BATU GORDANG DI DESA LIMBONG KECAMATAN SIANJUR MULA-MULA KABUPATEN SAMOSIR - Rudi Hambali Limbong (Universitas Negeri Medan, 2013)
This study aims to discuss the history of the discovery of stone Gordang. How to play rock Gordang and discusses the tone sounds on the stone gordaqng Limbong rural districts early Sianjur samosir district. Population and samples in this study amounted to 150 people in rural communities Limbong districts Sianjur samosir first district. The method used in this study is qualitative deskruptif. Data collection techniques used were observation, interviews and literature study documentation. Processing techniques and data analysis using qualitative descriptive research type. Simple in this research were 14 people districts Limbong Sianjur mula-mula district samosir. Author conducted research